'As pretty a thing as I have ever seen': animal encounters and Atlantic voyages, 1750–1850. (2nd July 2020) - McAleer, John
ABSTRACT: During the course of long voyages through the Atlantic Ocean – on their way to Africa, Asia and Australasia – British travellers experienced a variety of novel natural phenomena: the heat of the tropics, storms off the Cape, the beauty of shipboard sunsets, and unfamiliar constellations in the heavens. But it was the maritime animals that shared their shipboard space and inhabited the waters of the surrounding Atlantic that elicited the most sustained and detailed commentary from sailors and passengers. Animals were an integral part of these voyages. They travelled with passengers, as pets, curiosities and even speculative investments. The sea surrounding the ship was a veritable menagerie, encouraging travellers to speculate about the nature of the ocean and its inhabitants. They marvelled at strange creatures, compared them with familiar species, and collected them as specimens. As well as inspiring wonder and fear, encounters with maritime animals marked the journey from domestic and familiar to strange and unknown, expanding mental horizons in the process. Drawing on a wide range of first-hand accounts, this article explores the role played by maritime animals in marking the passage of travellers through the Atlantic in the Age of Sail.